The Impact of Fixed and Mobile Broadband Adoption on Economic Growth : A Panel Data Analysis - Endres, James; Steula, Mariana (Journal of Telecommunications and the Digital Economy, 2024)
This study analyses the impact of fixed and mobile broadband take-up on economic output for 34 OECD and G20 countries over the period 2008 to 2022. The results suggest that for the period both fixed and mobile broadband made positive contributions to a nation’s GDP per persons employed, with mobile broadband having the larger impact. The results also suggest that during the pandemic period (2020–2022) both fixed and mobile broadband were positively associated with GDP output. That said, many countries in the sample experienced notable declines in the take-up of mobile broadband during the pandemic period, resulting in a drag on GDP. This was offset, however, by increased take-up of fixed-line broadband services, which resulted in higher levels of economic output.